CONFLICT MANAGEMENT AND EMPLOYEE PERFORMANCE OF DEPOSIT MONEY BANKS IN NIGERIA: A STUDY OF DEPOSIT MONEY BANKS IN EDO CENTRAL SENATORIAL DISTRICT (American Journal of Research in Humanities and Social Sciences, 2023)
The study examined the relationship between conflict management and employee performance of Deposit Money Banks in Edo Central Senatorial District, Edo State. The study was anchored on Relational Dialectics Theory (RDT), introduced by Leslie Baxter and Barbara Matgomery (1988). Survey research design and primary data source were employed by the researcher. Questionnaire was used to elicit information from respondents of the deposit money banks in Edo Central, Edo State. A population of one hundred and seventy-two (172) was used by the researcher. Pearson Product Moment Correlation was used to analyze the collected data. Findings obtained from a test of the hypothesis reveals that there exists a strong significant positive relationship between collaboration strategy and employee performance (employee commitment) since r value=0.79 (79%). Based on the findings, the researcher concluded that there exists a strong significant positive relationship between Conflict Management and Employee Performance of the studied Deposit Money Banks in Edo Central Senatorial District, Edo State. Based on that, the researcher recommended that management of the studied deposit money banks should strive towards an effective adoption of collaboration strategy of conflict management as it could impact the performance level of employees.